Pharmacoepidemiology of Snake Bite Cases at a Tertiary Care Teaching Hospital in Odisha - Kunal Priyadarshi; Jayanti Prava Behera; Abinash Panda (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Snake bite is a neglected but widely distributed public health problem. It results in significant morbidity and mortality in many active young people which can be reduced with proper awareness, first aid and prompt hospital management. The present study institution is the only referral hospital in southern Odisha, serving most of the rural area cases, where the patients are mainly farmers or labourers. Odisha has a high number of fatalities accounting to 1000 snakebite deaths per annum. Not only has the rural and agricultural preponderance contributed to high mortality, but the lack of transportation service and loss of golden hour of treatment are the reasons. Aim: To assess the demographic characteristics, pharmacological interventions, with special reference to drug utilisation and risk factors associated with fatal outcomes in snake bite cases. Materials and Methods: This was a prospective, observational and hospital based study, carried out at emergency OPD and medicine IPD of MKCG MCH, Brahmapur, Odisha, from April to October 2016. Two hundered sixty cases of snake bite were included in this study, who satisfied the selection criteria and patient/ relative agreed to give written informed consent. Data regarding sociodemographic characters like age, sex, occupation, rural or urban area, of residence time elapsed after snake bite till hospitalisation, drug use and treatment outcome in terms of cure and death were collected in a case record form from hospital record and by interviewing to the relatives. The categorical data were expressed in percentage and risk factor associations were analysed by Chi-square test and Odds’ Ratio. Results: Out of the 260 cases, 56% cases belonged to 3060 years of age group and maximum number were males, accounting for 60% (156) cases. Majority of cases i.e., 85% (221) were from rural areas, of low socio-economic back ground i.e., 77% (200) and mostly illiterate. Prior to hospitalisation 58% (150) patients were treated using local remedies like traditional ayurvedic medicine or traditional healer. The case fatality was significantly associated with time elapsed from snake bite to administration of ASV, complications and initial dose of ASV for treatment and was observed to be 6.1% in this study population. Cobra bite constituted 16% of cases which had a significant association with mortality (p<0.001). Majority of cases (92%) received ASV within 1-6 hours and were significantly cured. But the patients who were treated with ASV after 6 hours i.e., 7.6%, showed significant association with fatal outcome (p<0.001). Conclusion: This study observed a direct association between different risk factors like delay in ASV administration, development of complications and initial dose of ASV and mortality. The study emphasises the need for improvement in transportation and ambulance service and proper sensitisation of general public with reference to appropriate first aid measures and undue reliance on traditional healers.